Potential lipolytic regulators derived from natural products as effective approaches to treat obesity - Yang, Xi-Ding; Ge, Xing-Cheng; Jiang, Si-Yi; Yang, Yong-Yu (Frontiers in Endocrinology, 2022)
Epidemic obesity is contributing to increases in the prevalence of obesity-related metabolic diseases and has, therefore, become an important public health problem. Adipose tissue is a vital energy storage organ that regulates whole-body energy metabolism. Triglyceride degradation in adipocytes is called lipolysis. It is closely tied to obesity and the metabolic disorders associated with it. Various natural products such as flavonoids, alkaloids, and terpenoids regulate lipolysis and can promote weight loss or improve obesity-related metabolic conditions. It is important to identify the specific secondary metabolites that are most effective at reducing weight and the health risks associated with obesity and lipolysis regulation. The aims of this review were to identify, categorize, and clarify the modes of action of a wide diversity of plant secondary metabolites that have demonstrated prophylactic and therapeutic efficacy against obesity by regulating lipolysis. The present review explores the regulatory mechanisms of lipolysis and summarizes the effects and modes of action of various natural products on this process. We propose that the discovery and development of natural product-based lipolysis regulators could diminish the risks associated with obesity and certain metabolic conditions.